1913 S.D. Sess. Laws 292, ch. 209, &sect - (:unkn) unknown (My University, 1913)
No person, firm, or corporation shall sell any dynamite or other high explosive, except ordinary gun powder in the state of South Dakota, to any person unknown to the seller, unless introduced by some person known to the seller, and on every sale the seller shall before delivery, make entry on a book kept for that purpose stating the date of sale, the name and address of the purchaser, the name and quantity of the article sold, the purpose for which it is required and the name of the person, if any, who introduced them. Any person failing to comply with the requirements of this section shall be deemed guilty of a misdemeanor.
1.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES